Exploring Dance Aesthetic in Contemporary Choreography at Universitas Negeri Gorontalo - Riana Diah Sitharesmi (Graduate School of Institut Seni Indonesia Yogyakarta, 2022)
In contemporary society, the creative concept of Indonesian choreography encounters the digitalisation and commercialisation, that can be both challenging and frightening. While young choreographers in Gorontalo are adjusting themselves in learning contemporary, they too need to appreciate traditional dance aesthetic, so they will have a clear concept while using ethnic elements in creating dance. One of the embodiments of North Sulawesi’s dance aesthetic is Dana Dana, developed in a limited way in Bolaang Mongondow. The similar dance is also existing in Gorontalo under the same name but slightly different in some components. As dance aesthetic is essential to construct the regional dance style, it is necessary to look further how the aesthetic of Bolaang Mongondow’s Dana Dana brings the distinctive features in the forms of choreographic development. Using a phenomenological approach integrated with creative-based choreographic, this research examined how the experimental and explorative works enrich the student’s experience to produce genuine vocabularies, and the embodiment of cultural values in their creation. Through a circle of observing-feeling-imagining-manifesting-forming, the concept of contemporary choreography embraces new artistic understanding that bring the transcendental realm of creativity. Mengeksplorasi Estetika Tari pada Koreografi Kontemporer di Universitas Negeri GorontaloAbstrakDalam masyarakat kontemporer, konsep kreatif koreografi Indonesia menghadapi tantangan digitalisasi dan komersialisasi, yang sekaligus menakutkan. Pada saat koreografer muda di Gorontalo sedang menyesuaikan diri dan mempelajari kontemporer, mereka juga perlu menghayati nilai-nilai budaya seperti estetika tari, sehingga mereka akan memiliki konsep yang jelas saat menggunakan elemen etnis dalam mencipta tari. Salah satu wujud estetika tari daerah Sulawesi Utara adalah tari Dana Dana yang dikembangkan secara terbatas di Bolaang Mongondow. Menarik, karena tarian serupa juga ada di Gorontalo dengan nama yang sama namun sedikit berbeda di beberapa komponen. Karena estetika tari sangat penting untuk membangun gaya tari daerah, maka perlu dilihat lebih jauh bagaimana estetika tari Dana Dana Bolaang Mongondow menghadirkan ciri khas dalam bentuk pengembangan koreografi. Menggunakan pendekatan fenomenologis yang terintegrasi dengan koreografi berbasis kreatif, penelitian ini mengkaji bagaimana kerja eksperimental dan eksploratif memperkaya pengalaman mahasiswa untuk menghasilkan kosakata gerak sejati, dan memberi wujud nilai-nilai budaya dalam penciptaannya. Melalui proses melingkar mengamati-merasakan- membayangkan-mewujudkan-membentuk, konsep koreografi kontemporer diarahkan untuk merengkuh pemahaman artistik secara baru yang membawa kreativitas pada ranah transendental.